Reproductive and developmental safety assessment of Ashwagandha (Withania somnifera) root extract in Wistar rats - Kalaiselvan, K.; Sweatha, V.; Gayathri, V.; Kalaivani, P.; Siva, R.; Tamrakar, Shonam (Frontiers in Pharmacology, 2025)
IntroductionAshwagandha (Withania somnifera L. Dunal), a popular botanical drug in Ayurveda, has a wide range of therapeutic applications. However, safety data for effects on reproduction and embryonic development in animal models is scarce. This randomized controlled study investigated the effects on body weight, reproductive organ weight, and thyroid hormone levels in pups of Wistar rats (10M/13F per group) who received oral aqueous Ashwagandha Root extract (500, 1,000, or 2,000 mg/kg/day body weight) or carboxymethylcellulose (control) for 4 weeks.MethodsAnimals were housed in polypropylene cages with males and females together during the pre-exposure and pre-mating periods. During the mating phase, one male and one female were kept together until confirmation of pregnancy. Pregnant females were housed individually during the post-mating period and lactating phase, while male rats were returned to their group cages. The procedure used was based on OECD Guideline 421 (OECD, 2016).ResultsThe No Observed Adverse Effect Level (NOAEL) in adult rats was 2,000 mg/kg. The mean body weights of pups and parental animals were similar (p > 0.05) in the treatment and control arms. Also, the weight of reproductive organs in parental male and female rats was similar (p > 0.05) in all groups.DiscussionThe parameters such as T4 and TSH levels, body weight, and weight of reproductive organs in adult Wistar rats and pups, were within range even at the maximum dosage. No evidence of toxicity at various stages of development and reproduction with aqueous extract was observed when administered orally. Rats’ ability to reproduce and develop was unaffected by standardized ashwagandha root extract.